2019
DOI: 10.3389/fpsyg.2019.00605
|View full text |Cite
|
Sign up to set email alerts
|

Positivity Effect and Working Memory Performance Remains Intact in Older Adults After Sleep Deprivation

Abstract: Background: Older adults perform better in tasks which include positive stimuli, referred to as the positivity effect. However, recent research suggests that the positivity effect could be attenuated when additional challenges such as stress or cognitive demands are introduced. Moreover, it is well established that older adults are relatively resilient to many of the adverse effects of sleep deprivation. Our aim was to investigate if the positivity effect in older adults is affected by one night of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…This finding agrees with previous observations showing that working memory capacity seems to be less rapidly affected by TSD (41 h of prolonged wakefulness) than sleepiness and sustained attention process (Lo et al, 2012; Slama et al, 2017). In agreement with Frenda and Fenn (2016), we can also suggest that TSD impairs cognitive processes by primarily inhibiting the ability of individuals to be alert and to sustain their attention, leaving their other cognitive functions under compensatory brain responses. This hypothesis relied on studies showing a better working memory performance at most difficult load after 35 h of TSD which was related to increased cerebral responses within parieto-frontal networks (Drummond et al, 2004, 2005b, 2012; Lythe et al, 2012).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This finding agrees with previous observations showing that working memory capacity seems to be less rapidly affected by TSD (41 h of prolonged wakefulness) than sleepiness and sustained attention process (Lo et al, 2012; Slama et al, 2017). In agreement with Frenda and Fenn (2016), we can also suggest that TSD impairs cognitive processes by primarily inhibiting the ability of individuals to be alert and to sustain their attention, leaving their other cognitive functions under compensatory brain responses. This hypothesis relied on studies showing a better working memory performance at most difficult load after 35 h of TSD which was related to increased cerebral responses within parieto-frontal networks (Drummond et al, 2004, 2005b, 2012; Lythe et al, 2012).…”
Section: Discussionsupporting
confidence: 88%
“…To a larger extent, studies showing either a morning time window of vulnerability for sustained attention processes (Cohen et al, 2010; Mollicone et al, 2010; Lo et al, 2012) or a differential kinetic between sustained attention and EFs (i.e., inhibition) in chronic sleep restricted subjects (Rabat et al, 2016) are also in accordance with this hypothesis. Intriguingly recently, Frenda and Fenn (2016) pointed out that pharmacological stimulants (i.e., caffeine, modafinil, and dextroamphetamine), logically awakening substances, are all efficient to compensate for sustained attention deficits related to TSD but not so for EFs (Wesensten et al, 2002, 2005; Killgore et al, 2009) [for review see (Frenda and Fenn, 2016)].…”
Section: Discussionmentioning
confidence: 99%
“…The time interval between the experience itself and recall may be more important. Gerhardsson et al (2019) found no impairment of WM in sleep-deprived elderly subjects but found differences in effects of SD on WM in people of different ages. In an electroencephalographic (EEG) study, memory performance worsened after SD and there was a significant change in the correlation between the left and right PFC, indicating that SD impairs memory by affecting the PFC (Li et al, 2014).…”
Section: Discussionmentioning
confidence: 68%
“…The main shortcoming of this study is that it only recruited young male subjects, so its results cannot be extrapolated to women or individuals in other age groups. Previous studies have shown that effects of SD on WM can vary with age (Gerhardsson et al, 2019). Therefore, subsequent research should include subjects of both sexes and a broader range of ages.…”
Section: Limitationsmentioning
confidence: 99%
“…Sleep quality is closely related to physical fitness, whereas long-term sleep disorders severely affect patient health. Sleep plays an important role in affecting and regulating mood and maintaining normal emotional memories (Cellini et al, 2019a; Gerhardsson et al, 2019; Jones et al, 2019; Lipinska et al, 2019). On the other hand, patients with sleep disorders are at risk for declarative memory deficits (Cassidy et al, 2017).…”
Section: Introductionmentioning
confidence: 99%